2020
DOI: 10.5210/ojphi.v12i1.10611
|View full text |Cite
|
Sign up to set email alerts
|

Improving Accuracy for Diabetes Mellitus Prediction by Using Deepnet

Abstract: Diabetes is a salient issue and a significant health care concern for many nations. The forecast for the prevalence of diabetes is on the rise. Hence, building a prediction machine learning model to assist in the identification of diabetic patients is of great interest. This study aims to create a machine learning model that is capable of predicting diabetes with high performance. The following study used the BigML platform to train four machine learning algorithms, namely, Deepnet, Models (decision tree), Ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For T2D risk prediction models, logistic regression has been frequently used and shown to be effective in supervised classification (Uddin et al, 2019; Xie et al, 2019). A recent study that compared machine learning models for the identification of patients with T2D reported logistic regression having the highest accuracy of 88.19% while decision trees had the lowest accuracy of 87.8% (Alshammari et al, 2020). Although studies that used extra trees for T2D risk prediction were not identified, the model is similar to random forest but contains random splits of observations which leads to lower levels of variance (Geurts et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For T2D risk prediction models, logistic regression has been frequently used and shown to be effective in supervised classification (Uddin et al, 2019; Xie et al, 2019). A recent study that compared machine learning models for the identification of patients with T2D reported logistic regression having the highest accuracy of 88.19% while decision trees had the lowest accuracy of 87.8% (Alshammari et al, 2020). Although studies that used extra trees for T2D risk prediction were not identified, the model is similar to random forest but contains random splits of observations which leads to lower levels of variance (Geurts et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is associated with premature deaths from both communicable and noncommunicable diseases. Therefore, early prediction of DM has great potential to reduce financial burden as well as increase life expectancy [4]. Machine learning is a growing field in healthcare for its promising performance in term of early prediction, diagnosis, classification, and risk stratification of diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the risk of human error when making important healthcare decisions. As a result, the health burden is reduced, and resources are better utilized (Alshammari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%